Аn improvement of process of organization of pedagogical practice is priority condition of forming of professional competence of future teachers the basics of health - S.І. Kara (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The problem of improving the organization of teaching practice as one of the primary conditions of formation professional competence of future teachers of basic health. Highlighted that the improvement of the process of organizing teaching practice can be done by improving the content of the students during the teaching practice, the organization of joint work of all supervisors (teachers of higher educational institutions and teachers of general educational institutions), compliance with the uniform requirements supervisors to an evaluation of the student's performance. It is noted that purposeful pedagogical guidance and to improve the content of the students during the teaching practice creates the conditions for the formation of all the components of professional competence of future teachers.